2016
DOI: 10.1002/phar.1856
|View full text |Cite
|
Sign up to set email alerts
|

Use of Tumor Necrosis Factor-Alpha Inhibitors in Children and Young Adults With Juvenile Idiopathic Arthritis or Rheumatoid Arthritis

Abstract: Earlier TNFI therapy was observed in 39.1% of children and young adults taking TNFIs. In addition, the time to the first TNFI prescription became shorter over the study period. Future research should evaluate the long-term effectiveness and safety of this more aggressive TNFI therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 41 publications
0
4
0
1
Order By: Relevance
“…ere are few reports on CRA in China, and most of them are small sample studies. Lee et al [10] reported that 48 children suffered from JDM, and 3 of them died of respiratory failure due to infection. Ince-Askan et al [11] thought that children with SLE were prone to serositis, and they were often positive when they were tested for antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…ere are few reports on CRA in China, and most of them are small sample studies. Lee et al [10] reported that 48 children suffered from JDM, and 3 of them died of respiratory failure due to infection. Ince-Askan et al [11] thought that children with SLE were prone to serositis, and they were often positive when they were tested for antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Drug persistence was defined as the time length of therapy until discontinuation, switch, or end of the study with a gap period of > 90 days, which has been used in other RA analyses. [35][36][37] We calculated total health care costs as the mean of all allowable costs for medical claims and pharmacy claims for each individual patient per 28 days. Because our drugs of interest were expected to comprise a large portion of total health care costs, we also calculated health care costs per member per month, excluding the cost for specialty RA agents, representing the total health care costs net of specialty RA agents.…”
Section: Discussionmentioning
confidence: 99%
“…If the index TNF-α blockers were switched to other TNF-α blockers or IL-17 inhibitors, or the index TNF-α blockers were restarted >90 days (permissible gap) after the last prescription, it was considered to be non-persistent to TNF-α blockers. Literature review indicated that 90 days permissible gap has been widely used for studying the long-term adherence of TNF-α blockers for the treatment of rheumatic diseases [ 7 , 42 , 43 , 44 , 45 ]. Causes of discontinuation of anti-TNF-α agents were classified as LOE, AE, and poor health literacy based on medical chart review.…”
Section: Methodsmentioning
confidence: 99%